Response of Date Palm Trees (Phoenix dactylifera L.) to Treatment with Boron and Silica Sol Nutrient Solution under Saline Growing Conditions - Hassan A. Faisal; Abdul Samad Aboud Abdullah; Ahmed Y. Lafta Hzaa (مجلة ديالى للعلوم الزراعية)
The objective of this study is to investigate the impact of different concentrations of boron 0, 100, and 200 mg L-1 and silica sol nutritional solutions 0, 3, and 6 mL L-1 on Khadrawi date palm trees in the presence of salt conditions. The results demonstrated that the spray treatment with boron at 200 mg L-1 and the spray treatment with silica sol nutrient solution at a level of 6 ml L-1 exhibited significant superiority. These treatments resulted in the highest values for various parameters including the concentration of mineral elements such as potassium, silicon, and boron, the ratio of potassium to sodium, the membrane stability index, the increase in activity of the peroxidase enzyme in leaves, the increase in the percentage of set, maturity, shoot weight, and total fruit yield. In contrast, the comparison treatment obtained the lowest values for these parameters. The treatments (boron at 200 mg L-1 and silica sol 6 mL L-1) decreased significantly, recording the lowest values in the concentration of sodium, chlorine, amino acids, proline, and ionic leakage of potassium ions in the leaves, while the comparison treatment recorded the highest values for the same traits. The interference between the two study factors significantly affected most of the studied traits.